Poly(N‐isopropylacrylamide) gel‐based macroporous monolith for continuous‐flow recovery of palladium(II) ions. Issue 4 (22nd September 2016) - Seto, Hirokazu; Matsumoto, Hikaru; Shibuya, Makoto; Akiyoshi, Takanori; Hoshino, Yu; Miura, Yoshiko
ABSTRACT: Macroporous monoliths, composed of thermoresponsive, tertiary‐aminated, and crosslinking monomers, were prepared for continuous‐flow separation of palladium(II) ions. N ‐Isopropylacrylamide was required to form the porous structure in the monoliths, indicating that the mechanism of porous structure formation involved polymerization‐induced phase separation of the poly( N ‐isopropylacrylamide) gel. Tertiary‐aminated monoliths showed adsorption selectivity for palladium(II) ions in hydrochloric media, compared with copper(II) ions. The maximum capacities of the monoliths with tertiary amine contents of 10, 20, 30, and 70 mol % for palladium(II) ions were 0.6, 1.1, 1.3, and 2.3 mmol/g, respectively. Darcy's permeabilities of water through the macroporous monolith were 10 −14 to 10 −13 m 2, and those were comparable to that through a commercially available membrane filter with a pore size of several micrometers. In the continuous‐flow process, the macroporous monolith with tertiary amine selectively adsorbed palladium(II) ions in the coexistence of copper(II) ions with 10 times higher concentration than the palladium(II) ions. The palladium(II) ions were eluted from the macroporous monolith, and the concentration of palladium(II) ions in the eluate was up to 45 times of that in the feed solution. The average enrichment factor and total recovery percentage of palladium(II) ions were 8.7 times and 95%, respectively. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44385. Abstract :